The effect of a Structured Clinical Instruction Module (SCIM) in pain on the learning outcome of third year medical students - San Buenaventura, Maricar L.; Maria Elizabeth M Grageda, PTRP MHPEd (2010)
A new method of teaching has been incorporated into the curriculum of third year medicine students of the Ateneo School of Medicine and Public Health which is Structured Clinical Instruction Module (SCIM). SCIM is an educational format intended to teach clinical and interpersonal skills. Previous studies showed that SCIM significantly improved assessment and management skills of students in Cancer Pain. As such, the study aims to determine the effectiveness of SCIM in increasing the knowledge, skill and attitude of third year Medicine students in the study of Pain. Moreover, it determines its effect as a learning tool on student performance, student's attitude towards learning, and teacher's perception, and compares student's performance using SCIM in Pain with those not using SCIM in Pain. Methods: The 66 third year medicine students were divided into two groups. The experimental group underwent lecture, small group discussion, reporting and Structured Clinical Instruction Module (SCIM) while the control group underwent lecture, small group discussion, reporting and rotation. Both groups took a test prior to and after completing the instructional methods. During SCIM, students' skill and attitude in history taking and physical examination of a pain patient were assessed. Their behavior from the beginning until the end of SCIM were noted. After the students have completed SCIM, they were asked to evaluate the teaching tool in terms of its ability to motivate learning, give valuable feedback and to self-assess their clinical skills using a four-point scale. Teachers participating in SCIM were likewise asked to evaluate SCIM using a four-point scale in terms of its ability to measure students' clinical skills, students' motivation in learning, provide valuable feedback, and its applicability. Results: T-tests to a significant difference in the pretest and posttest of students who were given SCIM (p-value of <0.001) and in the posttests of students given SCIM as compared to those who were not given SCIM (p-value of <0.001). Students strongly agreed that SCIM can prepare them for clerkship (p-value of 0.01), provides patient encounter for different diseases (p-value of 0.01), provides patient encounter for different diseases (p-value of 0.01), is a venue to apply skills in history taking and physical examination (p-value of 0.01), and teaches the proper assessment procedures for pain (p-value of 0.02). Teachers strongly agreed that it is a form of flexible teaching that adjusts instantly to treatment changes (three out of seven), labor intensive (four out of seven), and needs more time to prepare for (three out of seven). However, they disagree that it diminishes their importance in the learning process. Evaluation of the student's skill and attitude in history taking and physical examination of a pain resulted to a grade range of 80.64-93.56%. During SCIM, students were interested and engaged actively with the tasks and discussions involved in each station. Motivation in learning was exhibited by the students as shown by their good performance. Students expressed preference of SCIM over lecture, small group discussion, report and rotation because of SCIM offered more patient and teacher interaction, and valuable feedback. Conclusions: These results suggest that SCIM is an effective standardized instructional program that may enhance learning of clinical skills to students leading to better students' performance and favorable teachers' and students' perception towards learning.
Thesis (Master of Health Professions Education)--University of the Philippines Manila
Panel Members: Maria Elizabeth M Grageda PTRP MHPEd, Chair/Adviser; Erlyn A. Sana PhD, Reader/Critic; Melflor A. Atienza MD MHPEd, Member; Merle F. dela Cruz-Odi MD DPBA MBAH, Member; Blesilda E. Concepcion MD PPS MHPEd MBAH, Member.
Keywords: Medicine -- Curricula; Structured Clinical Instruction Module